The Hyperactive Child (Journal of Parents and Teachers, 2025)
The article refers to hyperactive children, exploring the causes of their behavior and the concepts of imperativity and impulsivity. It also presents a series of strategies and techniques that can serve as a guide for families and educators facing similar cases.
Keywords: hyperactivity; strategies; impulsivity; impulses